The revolt of the Zanj - Ṭabarī, 838?-923 (State University of New York Press, 1992)
Covering the years A.D. 869-79, details a rebellion in southern Iraq against the Abbasid caliphate that happened during the historian's lifetime. The latest in the 39-volume translation of al-Tabari's history of the Middle East, finished in A.D. 915. Well annotated. Paper edition (unseen), $16.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Translation of extracts from: Tārīkh al-rusul wa-al-mulūk.
Subtitle on half t.p.: A.D. 869-879/A.H. 255-265.
Keywords: Iraq -- History -- Zanj Rebellion, 868-883.; Islamic Empire -- History -- 750-1258.; Irak -- Histoire -- 868-883 (Révolte des Zandj); Empire islamique -- Histoire -- 750-1258.; HISTORY -- General.; Iraq; Islamic Empire; Abbasiden.; Irak.; Irak -- 0869-0883 (Révolte des Zandj); Empire islamique -- 750-1258.; 750-1258; History; Kronieken (vorm)